THE IMPACT OF AUDIT QUALITY CHARACTERISTICS ON ENHANCING ACCOUNTING CONSERVATISM-AN APPLIED STUDY ON IRAQI COMMERCIAL COMPANIES - Zaid Abdul Salam Muhammad; Murtadha Basil Ganim (Scholar Express Journals, 2025)
The purpose of the study is to determine how audit quality attributes, such as the audit firm's size, affect, duration of the relationship between the auditor and the client) on enhancing accounting conservatism in Iraqi commercial companies. A quantitative research methodology was used to fulfill the goals of the study. A sample was given a questionnaire that was created. selected using an appropriate sampling approach, consisting of (248) accountants and auditors working in commercial companies in Iraq, specifically in Baghdad Governorate. The data resulting from the survey were subsequently examined with the SPSS software. The findings demonstrated that the overwhelming majority of participants think that the length of the auditor-client relationship and the size of audit firms play a positive role in enhancing accounting conservatism in Iraqi commercial companies. This was proven by hypothesis testing, with a statistically significant effect between the variables. This indicates that increasing the quality of auditing, whether in terms of the audit firms' sizes or the long-term connection between the auditor and the client, increases the likelihood of companies adopting conservative accounting policies, which enhances the financial stability of companies and improves transparency and trust with stakeholders, including investors and shareholders.
Keywords: Audit quality characteristics; audit firm size; duration of auditor-client relationship